Workers' voice for better and sustainable corporate governance (Hans-Böckler-Stiftung, Institut für Mitbestimmung und Unternehmensführung (I.M.U.), 2018)
The Expert Group on "Workers' Voice and Good Corporate Governance in Transnational Companies in Europe" was initiated by the Hans-Böckler- Foundation in 2015 and assessed the extent and role of different forms of workers' voice in transnational companies. The academic report revealed that workers' voice is a key element of corporate governance in several European member states and is an asset in various ways.
Keywords: 330; Workers' Voice; Expert Group; Europe